2020
DOI: 10.1111/1440-1681.13434
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin IIb improved active chromatin‐induced systemic lupus erythematosus via balancing the percentage of Th17 and Treg cells

Abstract: The pathogenesis of systemic lupus erythematosus (SLE) is closely associated with aberrant immune system. Here, the aim of our study was to explore the regulation of cucurbitacin IIb (CuIIb) to Th17/Treg cells in SLE. Compared with normal mice, the percentage of Treg cells was downregulated in SLE mouse model, and Th17 was upregulated. Meantime, the production of Treg‐related transcription factor (foxp3) in SLE model mouse was reduced, and the production of Th17‐related transcription factor (RORγt) was increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In a study conducted in a lupus mouse model, the effect of Cucurbitacin IIb on Th17 and Treg cell percentages, Foxp3 and Ror-γt expression levels in cells isolated from the spleen of mice was investigated. As a result, it was observed that there was an increase in Treg cell population, decrease in Th17 cell population, increase in Foxp3 expression, decrease in Ror-γt expression, increase in IL-10 and TGF-β expression, and decrease in IL-17 and IL-6 levels in Cucurbitacin IIb applied groups compared to control [25].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a study conducted in a lupus mouse model, the effect of Cucurbitacin IIb on Th17 and Treg cell percentages, Foxp3 and Ror-γt expression levels in cells isolated from the spleen of mice was investigated. As a result, it was observed that there was an increase in Treg cell population, decrease in Th17 cell population, increase in Foxp3 expression, decrease in Ror-γt expression, increase in IL-10 and TGF-β expression, and decrease in IL-17 and IL-6 levels in Cucurbitacin IIb applied groups compared to control [25].…”
Section: Discussionmentioning
confidence: 94%
“…Oxidative stress and metabolic abnormalities have been found to related to the imbalance of Treg and Th17 in SLE [23,24]. In a SLE mice model Cucurbitacin IIb, an substrate extracted from a traditional Chinese medicine, found to be improved kidney injury by balancing the Treg(CD4 + Foxp3 + ) /Th17(CD4 + IL-17A + ) percentage in the meanwhile upregulated Foxp3 expression and downregulated Ror-γt expression in splenic lymphocytes [25]. Latest studies signify that attempts to reduce pathogenic Th17 cell population and increase Treg cell stability may provide promising therapeutic approaches in both SLE and RA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…8 A large number of studies have shown that due to the decrease in number of Tregs and increase in number of Th17 cells, Treg/Th17 ratio decreases, which negatively correlates with SLE disease activity. [36][37][38] In this study, the number of Tregs in the patients was lower than that of healthy individuals, while the absolute value of Th17 cells was higher. Therefore, the Treg/Th17 ratio was also significantly lower compared with healthy individuals, and the Treg/Th17 balance was tilted towards Th17.…”
Section: Immunology and Inflammationmentioning
confidence: 86%
“…CuIIb elicits antiproliferative effects in cervical (Vidal‐Gutiérrez et al, 2022) and lung cancer cells (Torres‐Moreno et al, 2020). It also induces apoptosis and cell cycle arrest via STAT3 and ameliorates active chromatin‐induced systemic lupus erythematosus (Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%